Conservative vs surgical management in ebstein's anomaly: long-term follow-up in a real-life cohort. (3rd October 2022) - Merino Argos, C; Meras Colunga, P; Ruiz Cantador, J; Jimenez Valero, S; Gonzalez Fernandez, O; Valbuena Lopez, S C; Ponz De Antonio, I; Rosillo Rodriguez, S O; Caro Codon, J; Iniesta Manjavacas, A M; Abelleira Pardeiro, C; Balbacid Domingo, E J; et al.
Abstract: Background: Ebstein's anomaly (EA) is a rare congenital heart disease that involves the tricuspid valve and the right ventricle, often associating atrial septal defects and atrial arrhythmias. Oligosymptomatic adults affected by this disease usually have good prognosis, while its evolution in symptomatic children is more aggressive. Clinical guidelines provide some recommendations for the former patients regarding surgical indication, but its evidence is scarce and benefit remains unclear. Purpose: To compare functional capacity, ventricular function parameters and outcomes between medically and surgically treated patients with EA. Methods: Retrospective cohort study of patients with EA followed-up in an adult congenital heart disease reference unit of a tertiary university hospital. Functional status and ventricular size and function parameters at baseline and follow-up, as well as clinical events, were compared between conservative and surgical groups. Results: We included 72 patients; mean age was 45.2±15.2 years and 27 (37.5%) were men. Median follow-up was 6.6 (range 0.3–20.3) years. Finally, 18 (25%) patients were operated (12 tricuspid repairs, 5 tricuspid bioprostheses and 1 mechanical tricuspid prostheses). Characteristics and outcomes of conservative and surgical group are shown in Table 1. Comparison of follow-up data for each group are shown in Table 2. Of note, Glenn procedure was done in 6 (33.3%) patients of the surgical group and prosthetic thrombosis was observed in 3 (50%) patients during follow-up. Conclusions: Only one fourth of patients with EA in our cohort were managed surgically. Operated patients had worse functional status and larger right ventricles at baseline. At follow-up, surgical patients had more clinical events and worse ventricular function. Exercise test parameters did not change significantly after surgery, whereas there was worsening functional capacity during follow-up in medically-managed patients. Funding Acknowledgement: Type of funding sources: None.